Migration and Home IMISCOE Short Reader - Fathi, Mastoureh; Ní Laoire, Caitríona (IMISCOE Research Series, 2024)
This open access short reader offers an intersectional perspective on the meaning of home in migration. The book provides a pathway through existing scholarship on home and migration, exploring how intersectional power relations and transnational migration regimes are felt, experienced, lived and navigated by migrants, who are differently positioned, in the making and imagining of home. The meanings associated with home are composed of the interrelation of places, spaces, people, social relations, materialities, emotions and temporalities. These multiple aspects highlight the complexities inherent in the idea of home, which come to the fore particularly when one moves location. Migration and Home explores these issues by focusing on specific key aspects of home in migration: home and gender; home and age; home and materiality; and home and migration status, class and race. It proposes the concept of structural im/possibilities as a framework for understanding the power relationsand structures that shape where, when and for whom home in migration is more, or less, possible.